2008
DOI: 10.1080/10253890801892040
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II AT1receptor blockade selectively enhances brain AT2receptor expression, and abolishes the cold-restraint stress-induced increase in tyrosine hydroxylase mRNA in the locus coeruleus of spontaneously hypertensive rats

Abstract: Spontaneously hypertensive rats, a stress-sensitive strain, were pretreated orally for 14 days with the AT 1 receptor antagonist candesartan before submission to 2 h of cold-restraint stress. In non-treated rats, stress decreased AT 1 receptor binding in the median eminence and basolateral amygdala, increased AT 2 receptor binding in the medial subnucleus of the inferior olive, decreased AT 2 binding in the ventrolateral thalamic nucleus and increased tyrosine hydroxylase mRNA level in the locus coeruleus. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 56 publications
(70 reference statements)
2
36
0
1
Order By: Relevance
“…Therefore, antagonists of this receptor are widely used to treat hypertension and cardiovascular related diseases. Several animal studies have also shown that independent of their beneficial effects on hypertension and cardiovascular related diseases, angiotensin receptor blockers can improve stress-related symptoms (15; 49; 50). A recent excellent review, highlights the beneficial effects of AT 1 antagonists on brain disorders and are suggested as potential therapy for neurodegenerative diseases such as Alzheimers (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, antagonists of this receptor are widely used to treat hypertension and cardiovascular related diseases. Several animal studies have also shown that independent of their beneficial effects on hypertension and cardiovascular related diseases, angiotensin receptor blockers can improve stress-related symptoms (15; 49; 50). A recent excellent review, highlights the beneficial effects of AT 1 antagonists on brain disorders and are suggested as potential therapy for neurodegenerative diseases such as Alzheimers (7).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that stressful situations can elicit an increase in plasma levels of renin, which catalyzes the formation of angiotensin, thus giving rise to elevated levels of circulating angiotensin II (1012). Animal studies have demonstrated that in response to immobilization and isolation stress, AT 1 receptor binding is increased in the paraventricular nucleus of the hypothalamus, and is reduced with ARBs (1315). More, recently lentiviral knockdown of the AT 1 receptor in the subfornical organ of the brain prevents the neuroendocrine response to restraint stress (16).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] These effects have been mainly attributed to differential changes in AT 1 and AT 2 receptor expression in the stress-responsive brain areas, both inside and outside the blood-brain barrier. [12][13][14] The AT 1 and AT 2 receptor subtypes are widely distributed in different brain areas, including the key areas controlling nociception, such as the anterior cingulated cortex (ACC), prefrontal cortex (PFC), thalamus, periaqueductal gray matter (PAG), amygdala, nucleus accumbens and spinal cord. [15][16][17] The PAG of the mid-brain region plays an important role in descending pain modulation by activating enkephalinreleasing neurons projecting to the raphe nuclei in the brainstem.…”
Section: Introductionmentioning
confidence: 99%
“…A similar treatment decreased anxiety in rats and prevented the stress-induced enhanced tyrosine hydroxylase transcription in the locus coeruleus, a measurement of central sympathetic stimulation [7,8]. These results implicate interactions between the central RAS, extrahypothalamic CRH systems, and GABA A in the regulation of anxiety and the behavioral responses to stress.…”
Section: Introductionmentioning
confidence: 69%